Wpływ warunków działania gospodarczego na udział małych i średnich przedsiębiorstw oraz inwestorów zagranicznych w strukturze PKB na przykładzie państw bałtyckich oraz Białorusi, Ukrainy i Mołdawii w latach 2004-2006 - Buszko, Andrzej (The Influence of Business Conditions Activity on the Share of Medium and Small Sized Companies and Foreign Investors in GDP in Baltic States and Ukraine, Belarus, Moldova, 2008)
The aim of this study is to compare the business conditions activity in Baltic States and Ukraine, Moldova, Belarus. The comparison was executed on establishing, handling and closing down the ltd. company. The comparison showed that the better conditions were in Baltic States than in the second group of companies. These results influenced the level of GDP and the share of medium and small sized companies and foreign investors in GDP.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 46-58